Impacts of Collaborative Logistics: A Brazilian Brewing Sector Case Study - Duarte Soliani, Rodrigo; Tiradentes Terra Argoud, Ana Rita; Santiago, Fábio; de Camargo Junior, João Batista; Gomes de Freitas, César; Pedroza Lobão, Mario Sérgio (International Journal of Industrial Engineering and Management, 2022)
Different organizations and institutions adopt Collaborative Logistics expecting to achieve a sustainable model in which the product serves society and generates profits. This research has the objective of identifying the impacts of collaborative logistics in the Brazilian brewing sector using a mathematical model that considers economic indicators and environmental ef- ficiency. Through a qualitative and exploratory methodology using the case study technique, results show a 100% increase in economic efficiency and a 40% reduction in CO2 emis- sions. The findings are relevant because they demonstrate that strategies of collaboration are recognized as the most effective approach for costs reduction and for sustainable business performance. Article history: Received (July 15, 2021); Revised (February 14, 2022); Accepted (February 22, 2022); Published online (March 1, 2022)